El etiquetado frontal en los alimentos y la iconografía jurídica: un ejemplo para la comprensión del trasplante jurídico y del nuevo paradigma latinoamericano - Ferrante, Alfredo (Pontificia Universidad Católica del Perú, 2021)
This paper analyzes the front-of-pack food labelling, with particular attention to Chilean, Colombian, Ecuadorian and Peruvian regulations (also de lege ferenda regulations). The aim is to contribute to a better understanding and use a comparative methodology, in particular of the figure of the legal transplant. In that sense, a concrete example of operability (not necessarily achieved) of a transplant is provided. The work also shows that the analyzedlegislations are far from European models and take Latin American standards as a reference, contributing to a paradigm shift in relation to the traditionalinfluence of foreign regulations that is usually incorporated into Latin American national systems.

Se realiza un estudio del etiquetado frontal en los empaques de alimentos en las regulaciones actuales y de lege ferenda de los ordenamientos chileno, colombiano, ecuatoriano y peruano, cuya finalidad es contribuir a una correcta comprensión y utilización de la metodología comparada, en particular de la figura del trasplante. En este sentido, se proporciona un ejemplo concreto de operabilidad (no necesariamente lograda) de un trasplante. También se destaca que las legislaciones analizadas se alejan de los modelos europeos y toman como referencia patrones propios de Latinoamérica, contribuyendo a un cambio de paradigma en relación con la tradicional influencia de la normativa extranjera que suele incorporarse en los derechos nacionales latinoamericanos.
Front-of-Pack Food Labelling and Legal Iconography: An Example of Legal Transplant and the New Latin American Paradigm
Keywords: Front-of-pack-labelling; Food; Comparative law; Comparative methodology; Legal transplant; Formate; Right to information; Consumer; Etiquetado; Alimentos; Derecho comparado; Metodología comparada; Trasplante; Formante; Derecho a la información; Consumidor; https://purl.org/pe-repo/ocde/ford#5.05.01